Model-Based educational technique to develop mathematical concepts in preschoolers - Vera V. Levites, Anna V. Beloshistaya, Nataliya V. Ivanch, Oleg I. Lyash, (Opción, 1970)
The article presents the results of a ten-year multi-stage pedagogical experiment on the development of mathematical concepts in hundreds of preschool children. It was proved that modeling should be considered as a methodology for the development of mathematical concepts in preschoolers. On the basis of this approach, an educational technique was developed for teaching mathematical concepts to preschool children. The result of teaching children with the technique is consistently high and has a prolonged effect. In conclusion, mathematics is a simple and understandable subject for the child where he can achieve significant success.